The effect of fishmeal on the growth and survival of milkfish (Chanos chanos) fry - Seneriches, Mary Lynn M. (Iloilo Graduate Faculty, University of the Philippines System, 1987)
The effect of adding animal sources of protein in the diets of milkfish fry was assessed by adding fraded levels of white fishmeal in diets containing corn gluten meal as the source of protein. Milkfish fry with an average weight of 8 mg were fed five diets formulated at 40% protein and with the same proximate composition for six weeks at 10% of body weight per day. Diet 1 was composed of corn gluten meal as the only protein source and essential amino acids found to be more than 10% lower than the profile of milkfish fry. Diets 2 and 3 contained corn gluten meal with fishmeal contributing 15% and 30% of the protein, respectively. The mneral and fat-soluble fraction equivalent to the amount used in diet 3 were extracted and added to the corn gluten mea lbasal diet 4 and 5 respectively. Growth was significantly higher (P<0.01) in fish fed diets with 30% of its protein from fishmeal (diet 3) than those given lower levels. Feed efficiency and survival in this treatment, was highest at 66.2% and 63% respectively but this did not significantly differ (P>0.05) from that of fish fed diets with 155 of its protein from fishmeal (diet 2). Poor growth responses, survival and feed efficiency were observed in fish fed diets containing corn gluten meal as the only source of protein. Further supplementation of this diet with mineral fraction (diet 4) or fat-souluble extract (diet 5) did not improve these parameters of measure. It is concluded that because of the high biological value fo fishmeal protein and the present inability to improve plant proteins to one of comparable quality, diets for milkfish fry should include no less than 15% of the protein from fishmeal to attain maximum growth, survival and feed efficiency.
Thesis (M. S. Fisheries-Aquaculture) -- Iloilo : University of the Philippines System, March 1987.
Keywords: Fish meal; Milkfish; Feeds; Fry